2023
DOI: 10.3389/fonc.2023.1034047
|View full text |Cite
|
Sign up to set email alerts
|

A LASSO-based model to predict central lymph node metastasis in preoperative patients with cN0 papillary thyroid cancer

Abstract: IntroductionCentral lymph node metastasis (CLNM) is common in papillary thyroid carcinoma (PTC). Prophylactic central lymph node dissection (PCLND) in clinically negative central compartment lymph node (cN0) PTC patients is still controversial. How to predict CLNM before the operation is very important for surgical decision making.MethodsIn this article, we retrospectively enrolled 243 cN0 PTC patients and gathered data including clinical characteristics, ultrasound (US) characteristics, pathological results o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Finally, 14 retrospective studies and two prospective study from 2012 to 2023 were included in our review. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Most studies were performed in Asian countries including 11 from China, two from South Korea and one from Saudi Arabia. Basic information was demonstrated in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 14 retrospective studies and two prospective study from 2012 to 2023 were included in our review. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Most studies were performed in Asian countries including 11 from China, two from South Korea and one from Saudi Arabia. Basic information was demonstrated in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular alterations associated with BRAF mutations influence PTMC initiation, progression, and metastasis. Some studies reported a high incidence of CLNM in patients with PTMC and BRAF mutations [ 21 , 25 ]. In the present study, BRAF status was also significantly associated with the risk of CLNM.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with several previous studies [30][31][32], our study found that youth, indistinct tumor boundaries, side of position and microcalci cation are also signi cant ultrasound features of total PLNM. Our ROC analysis in this study set the age diagnostic threshold at 45 years, where PTC patients ≤ 45 years old are more likely to present with CLNM [33,34]. Microcalci cations are mainly caused by calcium salt deposits resulting from vascular and brous proliferation, representing an accelerated growth of tumor cells.…”
Section: Discussionmentioning
confidence: 99%